Exploring the efficiency of Oxone®/KI as a promoter in the synthesis of spirocyclopropylbarbiturate derivatives via Michael-initiated reaction cyclization (MIRC) - Amin Rezaeifard; Eskandar Kolvari; Nadiya Koukabi (Results in Chemistry)
This study investigates the innovative use of Oxone®/KI as a a promoter in synthesizing spirocyclopropylbarbiturate (SCPB) derivatives via the Michael-initiated reaction cyclization (MIRC) process. The synthesis involves aromatic aldehydes, malononitrile, barbituric acid, Oxone®/KI, and sodium acetate in a water-ethanol mixture under standard conditions. This novel approach offers several key advantages, including a notably simplified purification process, milder reaction conditions, and significantly improved yields. These attributes contribute to greater efficiency, reduced labor intensity, and enhanced safety during synthesis. Importantly, the method also aligns with the principles of green chemistry, minimizing hazardous reagent use and waste generation. Collectively, these benefits position the Oxone®/KI system as a highly effective and environmentally responsible strategy for spirobarbiturate synthesis. The structural integrity of the synthesized derivatives was confirmed using FT-IR, 1H NMR, and 13C NMR spectroscopic techniques.